Melanin biopolymer synthesis using a new melanogenic strain of Flavobacterium kingsejongi and a recombinant strain of Escherichia coli expressing 4-hydroxyphenylpyruvate dioxygenase from F. kingsejongi - Lee, Han Sae; Choi, Jun Young; Kwon, Soon Jae; Park, Eun Seo; Oh, Byeong M.; Kim, Jong H.; Lee, Pyung Cheon (Microbial Cell Factories, 2022)
Background: Melanins are a heterologous group of biopolymeric pigments synthesized by diverse prokaryotes and eukaryotes and are widely utilized as bioactive materials and functional polymers in the biotechnology industry. Here, we report the high-level melanin production using a new melanogenic Flavobacterium kingsejongi strain and a recombinant Escherichia coli overexpressing F. kingsejongi 4-hydroxyphenylpyruvate dioxygenase (HPPD). Results: Melanin synthesis of F. kingsejongi strain was confirmed via melanin synthesis inhibition test, melanin solubility test, genome analysis, and structural analysis of purified melanin from both wild-type F. kingsejongi and recombinant E. coli expressing F. kingsejongi HPPD. The activity of F. kingsejongi HPPD was demonstrated via in vitro assays with 6 × His-tagged and native forms of HPPD. The specific activity of F. kingsejongi HPPD was 1.2 ± 0.03 μmol homogentisate/min/mg-protein. Bioreactor fermentation of F. kingsejongi produced a large amount of melanin with a titer of 6.07 ± 0.32 g/L, a conversion yield of 60% (0.6 ± 0.03 g melanin per gram tyrosine), and a productivity of 0.03 g/L·h, indicating its potential for industrial melanin production. Additionally, bioreactor fermentation of recombinant E. coli expressing F. kingsejongi HPPD produced melanin at a titer of 3.76 ± 0.30 g/L, a conversion yield of 38% (0.38 ± 0.03 g melanin per gram tyrosine), and a productivity of 0.04 g/L·h. Conclusions: Both strains showed sufficiently high fermentation capability to indicate their potential as platform strains for large-scale bacterial melanin production. Furthermore, F. kingsejongi strain could serve as a model to elucidate the regulation of melanin biosynthesis pathway and its networks with other cellular pathways, and to understand the cellular responses of melanin-producing bacteria to environmental changes, including nutrient starvation and other stresses.
Keywords: 4-Hydroxyphenylpyruvate Dioxygenase; Biopolymers; Escherichia coli; Flavobacterium; Melanins; Tyrosine; 4-Hydroxyphenylpyruvate dioxygenase; Flavobacterium kingsejongi; Melanin